2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20183155
|View full text |Cite
|
Sign up to set email alerts
|

A study of profile of contact dermatitis in housewives with reference to vegetables, soaps and detergents

Abstract: <p class="abstract"><strong>Background:</strong> Contact dermatitis in housewives is a common dermatological problem as almost all housewives have to handle vegetables, fruits, soaps and detergents. The purpose of this project was to study etiologic profile of contact dermatitis occurring in housewives.</p><p class="abstract"><strong>Methods:</strong> One hundred housewives, clinically diagnosed as having contact dermatitis, were randomly selected for the study. Each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Housewives are at an increased risk of contact dermatitis as they tend to handle fruits and vegetables as well as soaps and detergents. 54 Approximately 16% of contact dermatitis in housewives shows a fingertip eczema pattern, with secondary onychodystrophy characterized by onycholysis, Beau's lines, and chronic paronychia. 54,55 It has been reported that the main irritants correspond to detergents, followed by vegetables, particularly garlic and onion.…”
Section: Housewives Contact Dermatitismentioning
confidence: 99%
See 2 more Smart Citations
“…Housewives are at an increased risk of contact dermatitis as they tend to handle fruits and vegetables as well as soaps and detergents. 54 Approximately 16% of contact dermatitis in housewives shows a fingertip eczema pattern, with secondary onychodystrophy characterized by onycholysis, Beau's lines, and chronic paronychia. 54,55 It has been reported that the main irritants correspond to detergents, followed by vegetables, particularly garlic and onion.…”
Section: Housewives Contact Dermatitismentioning
confidence: 99%
“…54 Approximately 16% of contact dermatitis in housewives shows a fingertip eczema pattern, with secondary onychodystrophy characterized by onycholysis, Beau's lines, and chronic paronychia. 54,55 It has been reported that the main irritants correspond to detergents, followed by vegetables, particularly garlic and onion. 54 If not treated, the patient may experience intermittent painful episodes of acute inflammation plus esthetic discontent.…”
Section: Housewives Contact Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of cases of contact dermatitis to various vegetables, especially garlic and onion are described in homemakers indulging in peeling and cutting of raw vegetables, with duration varying from 1 month to 20 years 1–3 . Most patients present with erythema, scaling, and fissuring on the palmar aspect of tips of the thumb, index, and middle fingers of one or both hands, predominantly non‐dominant hand where the vegetable is usually held.…”
Section: Figurementioning
confidence: 99%
“…Patch test to ISS and allergens prepared from vegetables, detergents, and soaps was performed in 100 Indian females with contact dermatitis of the hands. Fifty‐five patients developed a positive reaction to vegetables, out of which 31 (56.6%) were allergic to garlic 1 …”
Section: Figurementioning
confidence: 99%